PENGARUH KUALITAS PELAYANAN PAJAK TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI (Studi Pada WPOP yang Terdaftar Di Kantor Pelayanan Pajak Pratama Pasuruan ) - Trianto, Andrian Agus (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
This study aims to obtain empirical evidence that tax service quality affects the individual tax payer compliance. Tax service quality is measured by direct evidence, reliability, responsiveness, assurance, and empathy. The research was conduct in KPP Pratama Pasuruan. The data obtained in the form of primary data and seconadary data. Primary data in this research is the research data obtained directly from the research by questionnaires. While secondary dataÂ obtained from data resources taken from KPP Pratama Pasuruan and supported with other literature. The research data were then tested by multiple linear regression using SPSS. The results showed the direct evidence, reliability, and assurance significantly influence the individual tax payer compliance. While responsiveness and empathy no significant effect on the individual tax payer compliance Keywords: Tax service quality and Individual tax payer compliance